Aplikasi Metode Spatial Multi Criteria Evaluation (SMCE) Untuk Perencanaan Lokasi Tempat Pemrosesan Akhir (TPA) Sampah di Kabupaten Kotabaru - muhammad firman wahyudi; Muhammad Firmansyah; Rizqi Puteri Mahyudin; Muhammad Husin (Jernih: Jurnal Tugas Akhir Mahasiswa, 2026)
Kotabaru Regency consists of 22 sub-districts with an area of 9,442.46 km2 and a population of 325,622 people in 2020. Kotabaru Regency has one TPA with an open dumping processing system, but these efforts are also not optimal due to the condition of open dumping waste storage holes. it is almost full and the population is increasing every year so that land suitability information is needed to develop a landfill site in Kotabaru District. Because of this, this plan was carried out to analyze suitable locations for landfill planning in Kotabaru district in eight subdistricts. This planning uses Geographic Information System (GIS) technology in the GIS there is a Spatial Multi Criteria Evaluation (SMCE) method. This planning refers to SNI 19-3241-1994 as a standard in determining the location of TPA. Analysis of the feasibility of the TPA location begins with an analysis of regional criteria with the principle of the regional binary method that matches the parameter with a value of 1 while those that are not suitable are given a value of 0, the result is 1,170.356 km2 and the results of the exclusion criteria are divided into 4 classes where class IV is stated as land suitability is very suitable with an area of 9,574 km2 which is spread over eight sub-districts in Kotabaru Regency. After the analysis was carried out, the location with the highest score was obtained in the pulau laut selatan in the village of Tanjung Seloka. However, this location is very far from the service area which will make it difficult to transport waste to the final waste processing location, so two alternative locations are recommended for the final waste processing site which are close to the service area, Sebelimbingan Village on the pulau laut utara and Selaru Village on the pulau laut tengah